"Le sentiment national est une barriere plus forte que toutes les lois": "la question juive" dans les debats du Parlement roumain (1866-1871) - Marton, Silvia (2007)
Abstract: The purpose of the paper is to analyze the debates in the Romanian Constitutional Assembly of 1866 concerning the article 7 of the Constitution that excludes non-Christians from political rights. It also examines the governmental regulations and the parliamentary questions to ministers on the discriminations and violence against the Jews during the years 1867-1869. The paper concludes that the Romanian legislators considered it to be of outmost importance to acknowledge the quality of being a Romanian, that is, a member of an ethnic body, and not to define citizenship as a legal membership. "To be a Romanian" was more of an ethnic belonging, a given, rather than citizenship or civic loyalty, defined through political and civic rights. Citizenship was crushed by the primordial character of ethnic loyalty and by the weight of the state as expression and guarantor of the Romanian nation. Furthermore, the paper holds that the parliamentarians' xenophobia and anti-Semitism is the expres